Influência do uso de dentifrícios a base de carvão ativado na estabilidade de cor e rugosidade de resina composta monocromática - Souza, Priscila Agustinha Neves de (2022)
This study aimed to investigate the influence of charcoal-based dentifrices on color change (ΔE00) and surface roughness (Ra) of a single-shade composite submitted to 12-month simulated brushing. One hundred and thirty-two bovine crowns were randomly allocated and restored with one of the following composites: SS- single-shade (Vittra Unique) or conventional multi-shade, NH- nanohybrid (Opallis), NF- nano-filled (Vittra APS), and BF- bulk-fill (Opus bulk-fill). Three dentifrices were evaluated: Control- conventional toothpaste (Colgate total 12), DC- a charcoal-based toothpaste (Natural Extracts), and PO- a charcoal-based toothpowder (Whitemax). The teeth were subjected to 1,217; 2,434; 7,300, and 14,600 brushing cycles, corresponding to T1- 1-month, T2- 2-month, T6- 6-month, and T12- 12-month simulated tooth brushing, respectively. The color (n=11, ΔE00) and surface roughness (n=11, Ra) were assessed at baseline and after each period of brushing time. The dentifrice and composite surface were analyzed by scanning electron microscopy (SEM). Color change and Ra data were analyzed by Three-way repeated measure ANOVA followed by the Tukey test (α=0.05). The interaction between brushing product*time was significant for ΔE00 (P<0.001) and time*brushing product*composite for Ra (P<0.001). Charcoal-based toothpaste alters the morphology, roughness, and color of single or multi-shade composites similarly to regular toothpaste. However, the toothpowder creates surface irregularities increasing color and roughness, with the greatest impacts on the nanohybrid composite surface as of 2-month simulated tooth brushing.